Germylone-bridged bimetallic Ir and Rh complexes - Su, Bochao (2021)
The reactions of germylone 1 with one equivalent of [M(COD)Cl]2 (M = Ir, Rh) afforded the germylone-bridged bimetallic complexes 2 and 3, which have been spectroscopically and structurally characterized. Density functional theory (DFT) studies reveal the relatively strong interactions between the Ge atom and these metals. By the reaction of [Rh(COD)Cl]2 with CO followed by addition of 1, a complex 4 involving a Rh–Ge–Rh–Ge–Rh chain was also synthesized.